Vaidika samājavāda - Agniveśa, Swami (Rājadharma Prakāśana, 1974)
On socialism according to Hindu points of view, with reference to the sociological approaches of Swami Dayananda Sarasvati, 1824-1883, founder of the Arya Samaj sect of Hinduism.